2022
DOI: 10.1080/1478422x.2022.2161122
|View full text |Cite
|
Sign up to set email alerts
|

Smart corrosion inhibitors for controlled release: a review

Abstract: Metal corrosion has been one of the most urgent problems bringing about great economic loss and life threats worldwide. Corrosion inhibitors can prevent metal from corrosion when directly added to corrosive media, which is a low-cost and efficient strategy towards corrosion protection. However, the corrosion protection ability cannot be durable without continuous additions of corrosion inhibitors. Micro/nano-containers encapsulated with corrosion inhibitors offer promising opportunities for delaying the corros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 116 publications
0
4
0
Order By: Relevance
“…Degradation of Mg-based alloys is always accompanied by hydrogen evolution, as shown in Eq. ( 1 ) [ 27 , 28 ]. …”
Section: Resultsmentioning
confidence: 99%
“…Degradation of Mg-based alloys is always accompanied by hydrogen evolution, as shown in Eq. ( 1 ) [ 27 , 28 ]. …”
Section: Resultsmentioning
confidence: 99%
“…In recent years, considerable progress has been made in the development of new corrosion-protection coatings and the formulation of various corrosion-resistant alloys (Pande and Parikh, 2013; Hasannejad et al , 2013; Suleiman et al , 2013; Wang et al , 2013; Kouhi et al , 2013). Some new developments provide effective means of reducing the damaging effects of corrosion on steel (Liu et al , 2020; Zhou et al , 2023a; Fakhri et al , 2023; Garcia-Cabezon et al , 2020; Gautam et al , 2022; Kaya et al , 2023).…”
Section: Introductionmentioning
confidence: 99%
“…They also observed that a water-based epoxy coating impregnated with modified TiO 2 containers exhibited enhanced self-healing characteristics. The use of smart corrosion inhibitors comprising micro/ nanocontainers has been reported to be highly effective compared with traditional corrosion inhibitors from the standpoint of long-term corrosion protection (Zhou et al, 2023a). Zeng et al (2022) developed a superhydrophobic coating that incorporated epoxy, silica nanoparticles and low-surface-energy siloxane.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon steel is extensively used for various applications due to excellent mechanical properties and low cost. However, carbon steel is highly susceptible to electrochemical deterioration when exposed to acidic environment and leads to catastrophic failure [1]- [3]. Corrosion inhibitor is an extensive approach to mitigate internal corrosion which generally occurs in hollow shapes such as oil and gas pipelines and storage containers.…”
Section: Introductionmentioning
confidence: 99%